High Efficiency and Power Tracking Method for Wireless Charging System Based on Phase-Shift Control - Vladimir Kindl; Martin Zavrel; Pavel Drabek; Tomas Kavalir (Energies, 2018)
The paper presents optimal operating point tracking algorithm for wireless charging system using identical coupling coils providing us to meet simultaneously high efficiency and high transmitted power under varied load and detuning conditions. The proposed method is suitable either for purely resistive load or battery load and it is based on phase-shift control between the primary and the secondary voltage. The paper also gives an intuitive mathematical description of the key control idea and demonstrates its operational abilities. The proposed algorithm is finally implemented into digital signal processor (DSP) and tested on 4 kW laboratory prototype of shielded wireless power transfer system.